БОРЬБА С КОРРУПЦИЕЙ В ПОЛИЦИИ В ЮГО-ВОСТОЧНОЙ АЗИИ: ПОЛИТИКА, УЧАСТИЕ И РЕФОРМА ГОСУДАРСТВЕННОГО УПРАВЛЕНИЯ - Нгич, Лор; Чо, Вонхюк (Вопросы государственного и муниципального управления, 2020)
As people’s interests and concerns on public safety have risen in Southeast Asia, academia has witnessed the growth of public management research on police corruption in the region. Little effort has been made to systematically analyse police corruption studies in Southeast Asia, therefore, we investigate what has been researched on police corruption in Southeast Asia in the field of public management. We present what research focuses there have been regarding anti-corruption measures and how they have changed over the last two decades, and then we offer suggestions for future research on this topic. Our analysis shows that political will was the most studied strategy in managing police corruption in the region, while anti-corruption agencies, police institutional reform and public participation have also been emphasized over time. Each Southeast Asian country places different emphases on these themes depending on the country’s unique context and experiences.